Association of physical activity, cardiorespiratory fitness, grip strength, and grip strength asymmetry with incident musculoskeletal disorders in 406,080 White adults - Yuexin Yu; Yulong Tang; Xiangnan Li; Zixin Hu; Li Jin; Jiucun Wang; Shuai Jiang; Hui Zhang; Jing Liu (Journal of Sport and Health Science, 2025)
Background: Musculoskeletal disorders (MSDs) represent a significant global health burden. While physical activity (PA) and physical fitness are both thought to reduce MSD risk, their independent and joint associations with MSD incidence have not been fully explored. This study investigated the independent and combined effects of PA, cardiorespiratory fitness (CRF), grip strength (GS), and GS asymmetry on MSD incidence in a large prospective cohort. Methods: We analyzed data from the UK Biobank cohort (2006–2023), including 406,080 participants aged 37–73 years (age = 55.7 ± 8.2 years, mean ± SD; 53.0% female) who were free of MSD at baseline and during the first 2 years of follow-up. PA, derived from self-reported data and expressed in total metabolic equivalent hours per week (MET-h/week); CRF (watts (W)/kilogram (kg)), measured using a cycling exercise test; and GS (kg), measured by hydraulic hand dynamometer, were included as exposures. GS asymmetry was defined by the left-to-right hand strength ratio. MSD incidence was determined via hospital records. Time-to-event associations were analyzed using Cox proportional hazards regression models with restricted cubic splines to account for non-linear relationships. The analysis was conducted in April 2024. Results: Over a median follow-up of 14.7 years, a total of 73,002 incident cases of MSDs were recorded (rheumatoid arthritis: 2923; osteoarthritis: 54,955; degenerative spinal diseases: 15,124). Lower self-reported PA (<4.8 MET-h/week) was associated with increased MSD risk (hazard ratio (HR) = 1.0710, 95% confidence interval (95%CI): 1.0623–1.0797). Low CRF (<1.22 W/kg; HR = 1.0941, 95%CI: 1.0596–1.1298), low GS (<27.80 kg; HR = 1.1133, 95%CI: 1.0990–1.1277), and GS asymmetry (HR = 1.1042, 95%CI: 1.0814–1.1274) were also significantly associated with increased MSD risk. Good CRF and GS, and lower GS asymmetry mitigated the higher MSD risk associated with low PA levels. Conclusion: Low levels of PA, CRF, GS, and GS asymmetry were associated with a higher risk of incident MSD. Meanwhile, improvements in CRF, GS, and GS balance could help offset the risk of MSD incidence in populations with insufficient PA.